Marketing practices of cooperative buying stations and private traders a comparative assessment study (Guimaras) - Pefianco, Jennifer C.
As part of SMISLE's market support services, the Programme has assisted three (3) cooperatives in establlishing mango-buying stations in Guimaras. The said project was established to provide market access to ackyard mngo grower and improve postharvest practices of the farmers thereby minimizing damages of fruit and maximizing profits. Three cooperatives namely: Nueva Valencia Multi-Purpose Cooperative (NVMPC), Jordan Framers Multi-Purpose Cooperative (JFMPC) and East Valencia Multi-Purpose cooperative (EVMPC) were recipients of the project for which SMISLE has provided for each, a buying station/packing house, weighing scales and plastic crates. Procurement fund amounting to â‚± 100,000.00 for each coop was also provided as procurement capital during the initial stage of the mango season in 1996. The project used a "pump-priming' mechanism for the fund provided for by SMISLE wherein the fund/capital can only be turned over to the cooperative if they match up the amount with net income earned from the project. An assessment was conducted to evaluate the performance of the mango buying project of the three cooperatives (NVMPC, EVMPC, JFMPC) based on the project's objectives, organizational and financial status as well as the cooperatives' marketing practices. At the same time, private traders marketing activities including services offered to the mango growers were gathered and compared with that of the cooperatives to determine in which market outlet served most beneficial to the growers. In terms of the services and assistance availed from both market agents, the private traders has the advantage since they provide for the growers' providential needs in the form of cash advance. Capital needs (cash and farm inputs) are given outright without any documentation and papers to fill out. While obtaining a loan from the cooperative requires considerable paperwork and extra time until capital needs are released. However, buying prices offered by the cooperative buying stations are relatively higher than of the private traders. Among other benefits offered by the cooperatives is patronage refund if the grower is a cooperative members and higher earnings in the long run.